Comparison of different surface pre-treatment on mild steel for cobalt-nickel-iron electroplating / Koay Mei Hyie … [et al.] - Koay, Mei Hyie; Mohd Fohimi, Nor Azirah; Budin, Salina; Che Maideen, Normariah; Abu, Md Zin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Electroplating is extensively practiced in the industry to fabricate corrosion-protective coatings for steel in large-scale production. Mild steel easily rusts at ambient temperature thus surface pre-treatment is mandatory to eliminate rust and superficial scale from the steel. Pre-treatment ensures that the steel surface is free from contaminants, which may interfere with the surface quality of the protective coating. This research is done to investigate the effect of different pre-treatment methods on the surface quality of mild steel rings and cobalt-nickel-iron coated mild steel rings. These surfaces were achieved by polishing the ring and subjected to alkaline degreasing, followed by immersion in sulfuric acid or sodium chloride at 10 vol % concentration and different immersion times (50 s, 55 s, and 60 s). Direct electroplating was applied to fabricate the cobalt-nickel-iron coating. The surface morphology of metal substrate and coating after electroplating were tested by scanning electron microscope (SEM), energy dispersive X-Ray (EDS), Vickers hardness, and surface roughness tests. Both types of pre-treatments provided lower surface roughness on the metal substrate and resulted in full coatings without voids formation. The results showed that pre-treatment using sulfuric acid exhibited higher hardness and a smoother coating surface. Agglomerates and cracking were observed on the surface coating treated with sodium chloride.